Bone health in children with primary hyperoxaluria type 1 following liver and kidney transplantation - Büscher, Rainer; Pape, Lars; Büscher, Anja K. (Frontiers in Pediatrics, 2024)
Background: Primary hyperoxaluria type 1 is leading to nephrocalcinosis, kidney stones, kidney failure and systemic oxalosis, including oxalate osteopathy. Combined liver-kidney transplantation (CLKT) and kidney after liver transplantation (KALT) were established options to stop the devastating consequences of oxalate bone disease. Methods: We describe 10 children with PH1 who were referred to us for combined transplantation. Demographic and clinical data were collected and symptoms of bone disease, conventional radiological examinations, plasma oxalate levels and determinants of calcium-phosphate metabolism were compared pre and post transplantation. Results: Ten patients (7 male, median age 5.8 years) were included in this study. Seven patients were diagnosed with infantile oxalosis and 9 patients received an intensified dialysis regime prior to transplantation. In one patient the transplanted kidney never achieved primary function and the boy remained on HD. All other patients remained without graft failure and retained stable kidney and liver function. Prior to transplantation, seven patients suffered from severe skeletal pain and three children presented with 1-3 series of pathological fractures. Pathological fractures did no longer occur in children who underwent successful CLKT or KALT. Plasma oxalate levels dropped within 6 months following Tx. Determinants of calcium-phosphorus metabolism did not differ significantly in comparison to other HD children. Seven of ten children showed a restricted growth at the time of transplantation and presented a moderate catch-up-growth at the time of last follow-up. Conclusions: Patients with PH1 suffer from severe consequences of a disturbed bone metabolism. However, bone health and growth can partially improve following CLKT/KALT.